Phytochemical Profiling and Granule Formulation of Green Betel Leaf (Piper betle L.) Extract for Potential Bio-Larvicidal Application - Meita Mahardianti; Puspa Rini Cahaya Nurani; Sekar Asri Tresnaningtyas; Suryadi Islami (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The increasing spread of Aedes aegypti as a vector of dengue disease has encouraged the exploration of safer, plant-based larvicidal materials. This study aimed to identify the phytochemical constituents of green betel leaf (Piper betle L.) extract and to develop a bio-larvicidal granule formulation as a modified dosage form. Phytochemical screening was conducted to identify bioactive compounds potentially associated with larvicidal activity. Methodology: Granules were prepared using the wet granulation method, employing polyvinylpyrrolidone (PVP) as a binder and lactose as a filler. The formulated granules were further evaluated through physical characterization tests, including flow rate, angle of repose, and dispersion time, to assess their suitability as a granular dosage form. Findings: The results demonstrated that all formulations exhibited acceptable flow properties, appropriate angles of repose, and rapid dispersion in water, indicating favorable handling and application characteristics. The flow rate test results showed that granules with concentration variations of 25%, 50%, 75%, and 100% exhibited flow rates of 71.4 g/s, 62.5 g/s, 50 g/s, and 45.5 g/s, respectively. Physical evaluation demonstrated that the granules had acceptable angles of repose (31°–36°) and dispersion time (20–25 seconds). Contribution: This study was conducted as a step toward developing an environmentally safe, natural-material-based biolarvicide